Programmed Cell Death in Cancer Progression and Therapy - Khosravi-Far, Roya; White, Eileen (Advances in Experimental Medicine and Biology, 2008)
Programmed cell death (PCD) plays pivotal roles in tumor progression, cancer therapeutics and resistance of tumor cells to therapy. With the discovery of key mechanisms that are involved in mediating PCD and in promoting resistance to therapy, design of therapeutic approaches for promoting tumor-selective cell death has risen dramatically. With this book, we give a comprehensive overview of the mechanisms that are involved in mediating and regulating PCD in cancer. We also provide a detailed indication of the utility of PCD in cancer therapy. This book will be a valuable resource for researchers investigating the role of PCD in cancer and other diseases, researchers investigating the molecular mechanism of chemotherapeutic agents and drug-resistance in cancer and for physicians using chemotherapeutic agents. Additionally, this book will be a important educational source for PhD students specializing in cell biology, immunology and MD students interested in Oncology and Cancer Therapeutics.